Computer Literacy Study: The Digital Divide Among New Students: A Case Study of the Undergraduate Program in Computer Science An Nasher University Cirebon - Yusep Saepulloh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation has shifted the educational paradigm but raised a serious challenge: the digital divide. At An Nasher University Cirebon, the